Land Use Change and Environmental Impacts: a Bibliometric Analysis - Santoso, Dian Hudawan; Puryani, Puryani; Algary, Tissia Ayu; Chaeron, Mochammad (Jurnal Pembangunan Wilayah dan Kota, 2025)
Land use change is a critical phenomenon that demands attention, particularly in metropolitan centers and developing cities in Asia and Southeast Asia that are undergoing substantial urbanization. The objective of this study is to examine the repercussions of land use modification on the environment, society, and economy. Additionally, it seeks to assess prevailing research trends in this domain through a bibliometric approach. The research methodology encompasses bibliometric analysis employing the Scopus database, encompassing the collection and filtration of data from 1986 to 2025, yielding 193 pertinent documents. The analysis indicates that publications in this field have exhibited significant an annual growth rate, reflecting a notable increase in scholarly interest in this subject. The study also found that China and the United States are the countries with the highest publication contributions, highlighting the importance of international collaboration in this research. The discussion revealed that land use change contributes to environmental degradation, biodiversity loss, and negative impacts on public health, particularly in developing countries. Moreover, this study identifies the need to expand studies in underrepresented countries and emphasizes the urgency of sustainable policies to address the challenges posed by land use change. The findings of this research are anticipated to offer insights that will inform the development of more effective and sustainable urban management and regional development policies by relevant stakeholders.